2020
DOI: 10.1016/j.molcel.2020.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Uses the DRD5-ARRB2-PP2A Signaling Axis to Block the TRAF6-Mediated NF-κB Pathway and Suppress Systemic Inflammation

Abstract: Highlights d Dopamine inhibits TLR2-induced NF-kB activation and inflammation via the DRD5 receptor d DRD5 can directly recruit TRAF6 and its negative regulator ARRB2 d DA-DRD5-ARRB2 signaling axis impairs TRAF6-mediated NF-kB activation and inflammation d DA-DRD5 signaling can protect mice against S. aureusinduced sepsis and meningitis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 41 publications
3
58
1
Order By: Relevance
“…While the role of dopamine in systemic inflammation is widely recognized, only recently it was shown that dopamine inhibits TRAF6-mediated NF-κB activation and inflammation via the D5 dopamine receptor in macrophages [ 185 ]. Through this mechanism, dopamine protected mice against S. aureus -induced sepsis and meningitis.…”
Section: The Immunomodulatory Role Of Dopaminementioning
confidence: 99%
“…While the role of dopamine in systemic inflammation is widely recognized, only recently it was shown that dopamine inhibits TRAF6-mediated NF-κB activation and inflammation via the D5 dopamine receptor in macrophages [ 185 ]. Through this mechanism, dopamine protected mice against S. aureus -induced sepsis and meningitis.…”
Section: The Immunomodulatory Role Of Dopaminementioning
confidence: 99%
“…D5R inhibits NF-kB signaling by mediating the negative regulation of ARRB2/PP2A on TRAF6-dependent signaling. A study found that D5R, via the EFD and IYX(X)I/L motifs in its CT and IC3 loop, respectively, can directly recruit TRAF6 and its negative regulator ARRB2, as well as downstream signaling proteins, such as TAK1, IKKs, and PP2A, to form a multiprotein complex, which impairs TRAF6-mediated activation of NF-kB (91).…”
Section: Nf-kb Signalingmentioning
confidence: 99%
“…Dopamine receptors are important players in the regulation of inflammation in the brain levels [39]. Recently, DRD5 has been shown to inhibit NF-kB activation and modulate levels of inflammation [40]. The increased DRD5 expression induced by ONC201 might reflect the contribution of this receptor signaling in returning macrophages to homeostasis after ONC201 treatment.…”
Section: Discussionmentioning
confidence: 99%